Balsamia - Uusi Ääni; Ainassaari, Jorma; Ainassaari, Kaisu; Anias, Outi; Collins, Katja; Hekkala, Tommi; Huotarinen, Johanna; Hyvärinen, Tytti; Kallio, Kirsti; Kangosjärvi, Hanna; Leskelä, Ekku; Marttila, Arto; et al. (Uusi Ääni, 2015)
12 kappaletta.